2003
DOI: 10.1080/10647440300025509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treating Bacterial Vaginosis on Preterm Labor

Abstract: Objective: Multiple studies suggest that bacterial vaginosis (BV) causes preterm labor; yet its routine treatment remains controversial. In order to help to elucidate this controversy, we performed a thorough review of studies with levels of evidence ranging from I to II-II. Methods:We searched for all of the studies from the years 1994 to 2001 via Medline's database, including MD Consult and Ovid Mednet. Results: Several trials discovered a decrease in the incidence of preterm labor when BV was treated, but m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…In addition, the intrauterine infection, which may have originated in the vaginal cavity, might account for 25-40% of preterm births [59]. The most commonly associated bacteria are bacteria from the class Mollicutes (Ureaplasma species, Mycoplasma genitalium, and M. hominis, for example) [60,61], but many other microbial species have been identified in cases of bacterial vaginosis, including Prevotella [62][63][64]. Those microbes might invade the uterus by migrating from the passage through the cervix from the vagina and infect the amniotic fluid [59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intrauterine infection, which may have originated in the vaginal cavity, might account for 25-40% of preterm births [59]. The most commonly associated bacteria are bacteria from the class Mollicutes (Ureaplasma species, Mycoplasma genitalium, and M. hominis, for example) [60,61], but many other microbial species have been identified in cases of bacterial vaginosis, including Prevotella [62][63][64]. Those microbes might invade the uterus by migrating from the passage through the cervix from the vagina and infect the amniotic fluid [59].…”
Section: Discussionmentioning
confidence: 99%
“…It should therefore come as no surprise that treatment with oral or vaginal metronidazole, which efficiently kills anaerobes, but not aerobic bacteria, reduces BV in pregnancy, but fails to decrease the risk of PPROM or PTB in randomised, placebo-controlled series. [29][30][31] Carey et al 2 re-analysed their data after they failed to find a protective effect of metronidazole in a large population-based placebo-controlled treatment trial. They found that, at delivery, Klebsiella and E. coli were more often present in the flora of women delivering preterm than in the flora of other women.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in case–control studies of women in labour investigating the difference between typical bacterial vaginosis with overgrowth of Gardnerella vaginalis /anaerobes and the presence of other abnormal flora types, an association between BV in labour and subsequent PTB was consistently lacking, while the association of PTB with the presence in labour of Klebsiella sp., E. coli , staphylococci and streptococci, 2,24 with or without signs of inflammation or neutrophils in the vagina, 25–28 was rather strong and consistent. It should therefore come as no surprise that treatment with oral or vaginal metronidazole, which efficiently kills anaerobes, but not aerobic bacteria, reduces BV in pregnancy, but fails to decrease the risk of PPROM or PTB in randomised, placebo‐controlled series 29–31 . Carey et al 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Some antibiotics showed increased risk of delivery < 37 weeks (RR with metronidazole versus placebo 1.6, 95% CI 1.05 -2.4) (74). Antibiotics are therefore only recommended in women with P-PROM because they are effective in restoring vaginal flora73, but not as prophylaxis in high-risk asymptomatic women (66,75,76). A review of all UK PSCs reflects this, as no centres used antibiotics prophylactically.…”
Section: Antibioticsmentioning
confidence: 99%